ADIPSIC DIABETES INSIPIDUS IN LOCALLY ADVANCED NASOPHARYNGEAL CARCINOMA - Firhan, H; Syakir, Y Ahmad; Phang, YR; See, CK (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION Pituitary metastasis in nasopharyngeal carcinoma (NPC) is extremely rare with early detection and presentation of NPC. Up to 30% of patients present with diabetes insipidus (DI). The inability to sense thirst or adipsic DI may result in electrolyte imbalance and hypovolemia. RESULTS A 29-year-old woman presented with a short history of dysphagia and hoarseness of voice followed by a week of right eye and facial swelling. Further enquiry revealed a one-year history of unexplained epistaxis and loss of appetite, and weight loss of 5 kg in one month. Physical examination revealed right cranial nerve II to VI, VIII and bulbar palsies. Nasopharyngeal assessment showed a mass over the right posterior choana with right vocal cord palsy. She was admitted to the ENT ward for a suspicion of nasopharyngeal carcinoma with intracranial extension. Initial preoperative medical review revealed persistent tachycardia and significant polyuria. Subsequent diagnosis of central DI was confirmed with findings of high serum osmolality, low urine osmolality and hypernatremia.Tachycardia was attributed to hypovolemia and responded to fluid correction. Intermittent doses of desmopressin controlled urine output and improved hypernatremia. As the patient could not sense thirst, she was unable to actively consume fluids. There was extreme difficulty in normalising her sodium and maintaining hydration. Delicate balance of supervised fluid consumption with supportive intravenous fluids and desmopressin was required. Cranial MRI later confirmed a locally advanced nasopharyngeal tumour with pituitary gland and stalk metastasis and invasion into both cerebello-pontine angles and hypothalamus. Her initial anterior pituitary hormone function was intact. CONCLUSION DI in a locally advanced nasopharyngeal carcinoma is a poor prognostic indicator. The presence of adipsic diabetes insipidus further complicate the delicate management of hydration and sodium balance in such patient.